Unravelling Gender Inequality: A Semiotic Analysis of Taylor Swift's Song Lyrics - Fadila, Wildania; Nisa, Baiatun (Universitas Muhammadiyah Tangerang, 2024)
This study aims to explore the semiotic representations of gender inequality within Taylor Swift's song lyrics. Utilizing a descriptive qualitative method, it analyzes the signifier and signified embedded in her music. Drawing upon Ferdinand de Saussure's semiotic theory, the study delves into the material aspects of language—what is seen, heard, or read (signifier)—and the corresponding mental images or concepts (signified). Through a comprehensive analysis of Swift's songs, including